2017
DOI: 10.2147/dddt.s138926
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic testing and new validated HPLC method to assess the interchangeability between multi-source orlistat capsules

Abstract: BackgroundOrlistat is an irreversible inhibitor of the lipase enzyme that prevents trigylcerides from being digested, thereby inhibiting triglyceride hydrolysis and absorption. The resultant reduced calorie uptake enables a positive effect on weight control. Systemic absorption of the drug is, therefore, not necessary for its mode of action. An alternative in vitro study (pharmacodynamic) has been introduced for this drug, as in vivo bioavailability studies are irrelevant with regard to the achievement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…To explore the relationship between fucoidan and the substrates (4‐nitrophenyl laurate) and orlistat, molecular docking analyses of orlistat and 4‐nitrophenyl laurate with pancreatic lipase were performed. Previous studies have shown that orlistat is an irreversible active site inhibitor of lipase 38 . Docking results showed that orlistat binds directly to the active center of pancreatic lipase with a binding free energy of −7.3 kcal mol −1 , binds with van der Waals forces to HIS264 in the active site, and forms hydrogen bonds with residues PHE78, HIS152, GLY77, and SER153, of which SER153 is also a critical amino acid in the active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the relationship between fucoidan and the substrates (4‐nitrophenyl laurate) and orlistat, molecular docking analyses of orlistat and 4‐nitrophenyl laurate with pancreatic lipase were performed. Previous studies have shown that orlistat is an irreversible active site inhibitor of lipase 38 . Docking results showed that orlistat binds directly to the active center of pancreatic lipase with a binding free energy of −7.3 kcal mol −1 , binds with van der Waals forces to HIS264 in the active site, and forms hydrogen bonds with residues PHE78, HIS152, GLY77, and SER153, of which SER153 is also a critical amino acid in the active site.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that orlistat is an irreversible active site inhibitor of lipase. 38 Docking results showed that orlistat binds directly to the active center of pancreatic lipase with a binding free energy of −7.3 kcal mol −1 , binds with van der Waals forces to HIS264 in the active site, and forms hydrogen bonds with residues PHE78, HIS152, GLY77, and SER153, of which SER153 is also a critical amino acid in the active www.soci.org C Lu, Q Gu, X Yu wileyonlinelibrary.com/jsfa site. The free energy of binding of 4-nitrophenyl laurate to pancreatic lipase is −6.1 kcal mol −1 , forming a hydrogen bond with amino acid residue SER153 in the active site.…”
Section: Molecular Docking Of Fucoidan With Pancreatic Lipasementioning
confidence: 99%
“…Orlistat is a carboxylic ester resulting from the formal condensation of the carboxy group of N-formyl-leucine, which is practically insoluble in water and slightly soluble in methanol. 3 It also improves insulin sensitivity and reduces body fat and serum leptin levels. Orlistat is a semisynthetic derivative of lipstatin; it is a potent and selective natural inhibitor of gastric and pancreatic lipases, which play an essential role in the digestion of dietary fat.…”
Section: Fig 1: Structure Of Orlistatmentioning
confidence: 99%
“…Despite numerous advantages of this drug, researchers are facing problems for estimation by HPLC because limited methods are available; only United State Pharmacopoeia (USP) method is the most reliable and effective. In the literature, there is an HPLC method for the determination of Orlistat in human plasma for pharmacokinetics studies 3 . However, there is no method for quantifying Orlistat in pharmaceutical dosage forms, especially in the floating drug delivery system.…”
Section: Fig 1: Structure Of Orlistatmentioning
confidence: 99%
“…O método utilizado consiste em hidrolisar o substrato p-NPP na presença da lipase, formando o p-nitrofenol (p-NP) e o ácido palmítico (Figura 19). A extensão da inibição da lipase tem um impacto negativo na quantidade de p-NP liberado, sendo esta, medida espectrofotometricamente (ZAID et al, 2017).…”
Section: -Atividade De Inibição Da Lipase Pancreáticaunclassified